2013
DOI: 10.1099/mic.0.070029-0
|View full text |Cite
|
Sign up to set email alerts
|

Culture-independent sequence analysis of Chlamydia trachomatis in urogenital specimens identifies regions of recombination and in-patient sequence mutations

Abstract: A culture-independent genome sequencing approach was developed and used to examine genomic variability in Chlamydia trachomatis-positive specimens that were collected from patients in the Seattle, WA, USA, area. The procedure is based on an immunomagnetic separation approach with chlamydial LPS-specific mAbs, followed by DNA purification and total DNA amplification, and subsequent Illumina-based sequence analysis. Quality of genome sequencing was independent of the total number of inclusion-forming units deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…In addition, it has been shown that extended in vitro culturing of other chlamydial species may alter the genotype of these isolates (15). Due to these issues, culture-independent methods have been devised to sequence Chlamydia genomes directly from clinical swabs (17,18). In this study, a probe hybridization sequence capture method was used to extract C. pecorum DNA from swab samples collected from koalas and Australian sheep and a cell-cultured Australian bovine isolate (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been shown that extended in vitro culturing of other chlamydial species may alter the genotype of these isolates (15). Due to these issues, culture-independent methods have been devised to sequence Chlamydia genomes directly from clinical swabs (17,18). In this study, a probe hybridization sequence capture method was used to extract C. pecorum DNA from swab samples collected from koalas and Australian sheep and a cell-cultured Australian bovine isolate (20).…”
Section: Discussionmentioning
confidence: 99%
“…In a major breakthrough in the Chlamydia research field, cultureindependent sequencing methods have been developed, with one of the first approaches involving immunomagnetic separation (IMS) of chlamydial cells using antibodies specific for the chlamydial lipopolysaccharide (16). Using IMS in conjunction with multiple displacement amplification (MDA) produced whole-genome sequences for C. trachomatis strains from low-volume archival samples and swab samples collected from patients (17,18).Sequence capture by hybridization also can be used to sequence chlamydial DNA without the need for cell culturing (19). The sequence capture method involves designing customized biotin-labeled RNA probes that can hybridize to a complete target genome sequence so that magnetic beads coated with the biotinbinding protein streptavidin can be used to extract the captured sequences (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Single-end 100-bp sequencing was performed on an Illumina HiSeq 2000 sequencing system at the Center for Genomic Research and Biocomputing Core, Oregon State University, Corvallis, OR. Genome sequences were assembled and analyzed as described previously (45). Mutations were confirmed by PCR amplification of the corresponding genomic regions and Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…HeLa cells infected with various mutants were harvested by bead agitation in SPG, and the lysate was clarified by centrifugation at 500 ϫ g for 20 min. Host cell genomes were depleted by DNase treatment (45), and the remaining DNA was amplified with REPLI-g (Qiagen) according to the manufacturer's instructions. Whole-genome sequencing (WGS) libraries were prepared using a Nextera XT DNA library preparation kit according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%